Analisis Kinerja Ruas Jalan Diponegoro Kota Blitar - Motu, Lukas Laiya; Pandulu, Galih Damar; Primasworo, Rifky Aldila (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
This study aims to determine the characteristics of the Diponegoro road and to recognize the performance of the road. This study utilizes descriptive methods and Guidelines for Indonesian Road Capacity (PKJI, 2014). The results revealed that the value of the Degree of Saturation (DJ) was 0.340 on weekdays in the morning peak hours with service level category B. Meanwhile, during peak hours in the afternoon and evening each had a Degree of Saturation (DJ) value of 0.301 and 0.205 with service level category B. The value of the Degree of Saturation (DJ) on weekends in the morning, afternoon and evening peak categories are 0.226, 0.193 and 0.153, respectively, with service level B. Meanwhile, the prediction for the next 5 years (2029) The Degree of Saturation (DJ) is 0.386 during peak hours. in the morning with service level category B and on weekends the Degree of Saturation (DJ) is 0.257 in service level category B. This level of service needs to be continuously improved by increasing pedestrian facilities and providing vehicles outside the road to maintain the value of side barriers with a very low category.